Association between systemic inflammation and water composition and survival in colorectal cancer - Lin, Shi-Qi; Xie, Hai-Lun; Ge, Yi-Zhong; Ruan, Guo-Tian; Zhang, Qi; Song, Meng-Meng; Zhang, He-Yang; Zhang, Xi; Li, Xiang-Rui; Tang, Meng; Shen, Xian; Song, Chun-Hua; et al. (Frontiers in Oncology, 2022)
Background Systemic inflammation and water composition are important factors affecting cancer prognosis. This study aimed to explore the association between the neutrophil-to-lymphocyte ratio (NLR) and intracellular water/total body water (ICW/TBW) ratio and overall survival (OS) in colorectal cancer (CRC). Methods This multicenter, prospective cohort included 628 patients with CRC between June 2012 and December 2019. The association between the covariates and OS was assessed using a Cox proportional hazards model and restricted cubic spline models. Concordance index (C-index), which integrated discriminant improvement (IDI) index and continuous net reclassification index, (cNRI) was used to compare the predictive ability of the markers. Results The optimal cutoff values for the NLR and ICW/TBW ratio were 2.42 and 0.61, respectively. The NLR was negatively associated with OS, while the ICW/TBW ratio was positively correlated with OS. NLR ≥2.42 and ICW/TBW ratio <0.61 were both independent poor prognostic factors (hazard ratio [HR]: 2.04, 95% confidence interval [CI]: 1.44–2.88 and HR: 1.45, 95% CI: 1.04–2.02, respectively). Subsequently, we combined the two factors to construct an inflammation-water score (IWS). Patients with IWS (2, ≥1) had worse OS (HR: 2.86 and 95% CI: 1.77–4.63; HR: 1.74 and 95% CI 1.17–2.57, respectively) than those without one. Compared to its component factors, IWS score showed better predictive ability for C-index, IDI index, and cNRI. Conclusion A high NLR and a low ICW/TBW ratio were independent risk factors for poor prognosis in patients with CRC. The combination of the two factors can provide a better prognostic prediction effect.